The book of Lamentations - Goldingay, John (New International Commentary on the Old Testament (NICOT), 2022)
Intro -- Title Page -- Copyright -- Contents -- Series Editor's Preface -- List of Abbreviations -- Bibliography -- Introduction -- I. Background -- II. Unity of Composition -- A. The Unity and Interrelationship of the Poems -- B. Poetic Form in the Poems -- C. The Relationship between the Cola -- D. Repetition, Terseness, Imagery, Point of View, Genre -- III. Authorship and Date -- IV. Occasion, Place of Origin, and Destination -- V. Canonicity -- A. The Canonical Process -- B. The Bounds and the Order of the Canon -- VI. The Hebrew Text -- VII. Theology -- VIII. Main Themes and Their Implications -- A. The Explosion of Interest -- B. Theodicy and Antitheodicy -- IX. Analysis of Contents -- Text and Commentary -- Lamentations 1: "Is There Pain like My Pain?" -- Lamentations 2: "He Poured out His Wrath like Fire" -- Lamentations 3: "Perhaps There is Hope" -- Lamentations 4: "He Lit a Fire in Zion" -- Lamentations 5: "Be Mindful, Yahweh".